Liderazgo y aseguramiento de la calidad en universidades: un análisis de la designación de autoridades y el desempeño institucional con registros administrativos del sistema universitario peruano - Etesse, Manuel (2026)
This exploratory study examines the relationship between the appointment of interim authorities and compliance with Basic Quality Conditions in the Peruvian university system. The objective is to determine whether instability in leadership positions affects institutional performance during the Institutional Licensing process (2015-2020). To identify correlations, a multivariate analysis with postestimations was conducted using administrative data from 125 universities evaluated during this period. A higher prevalence of interim authorities is significantly associated with lower probabilities of obtaining the operating license, even after controlling for various institutional characteristics. This pattern is particularly notable in recently established universities, smaller institutions, and those under private corporate management. The findings suggest that leadership instability hinders the continuity of policies and quality assurance strategies. The study underscores the importance of reviewing and strengthening the mechanisms for appointing senior authorities. It emphasizes that stable institutional leadership is essential to ensuring continuous improvement in educational quality within a university system marked by structural fragility.